HUBUNGAN KEIKUTSERTAAN KELAS IBU HAMIL DENGAN PERILAKU IBU DALAM PERAWATAN MASA NIFAS (Studi di Puskesmas Cepiring Kabupaten Kendal) - Anisatul Khofidzoh; M. Zen Rahfiludin; Martha Irene Kartasurya (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Maternity class which aimed to decrease maternal mortality rates, has been implemented in Kendal District since 2010. Maternity class in Cepiring (one of the primary health care center in Kendal) has been held in 15 places but the rates of postpartum visit (KF3) still low in 2014. The research objective was to analyze the association between the maternity class attendance and knowledge, attitude and practice of postpartum careamong post partum mothers inCepiring Primary Health Care Center working area. This study was an explanatory study with a cross-sectional approach. The population was 204 postpartum mothers who lived in Cepiring during January-March 2016. Among them 66 subjects were chosen through purposive sampling method. Data were analyzed by Chi Square tests. The results showed that precentage of postpartum mother’s with low konwledge was 54.5%, postpartum mother’s with good attitude was 68.2%. postpartum mother’s with good practice was 57.6%. There were associations between the maternity class attendance and knowledge (p=0.002) and attitude (p=0.013). There was no association between the maternity class attendance and postpartum care practice (p=0.646). It is concluded that the maternity class attendance was associated to knowledge and attitude in postpartum care. It was suggested that the midwives motivate the postpartum mothers to attend the maternity class and apply their knowledge of post partum care in practice.